A deficit in post-graphemic writing processes: Evidence for a graphomotor buffer. Issue 8 (17th November 2018) - McCloskey, Michael; Reilhac, Caroline; Schubert, Teresa
ABSTRACT: Post-graphemic writing processes transform abstract letter representations into representations of writing movements. We describe an individual with an acquired post-graphemic writing deficit. NGN is normal in spelling words aloud, but impaired in writing words to dictation, with most errors involving letter substitutions (e.g., RUMOR written as BUMOR). NGN's deficit affects graphic motor plans, which specify the writing strokes for producing letters. Analyses of writing speed, fluency, and stroke patterns suggest that NGN's errors result from incomplete motor-plan activation. NGN's error rate is high for the first letter in a word, and declines across subsequent positions. On the basis of this serial position effect and other results, we propose that post-graphemic writing mechanisms include a graphomotor buffer, a writing-specific working memory that holds activated graphic motor plans bound to specific serial positions. We suggest that NGN's graphomotor buffer is damaged such that early serial positions are affected most severely. Finally, we present results speaking to the roles and capabilities of the graphomotor buffer, and the structure of graphic motor plans.